Monodisperse nano-metal dispersion and rapid continuous green synthesis method thereof

By combining a supergravity reactor and plant extracts, the complexity and dispersibility issues of nanomaterial preparation methods have been solved, enabling rapid, continuous, and green synthesis of monodisperse nanomaterial dispersions, which are suitable for the high stability and large-scale production of various metal particles.

CN120901279APending Publication Date: 2025-11-07BEIJING UNIV OF CHEM TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511033003.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing methods for preparing nanomaterials suffer from problems such as complex processes, insufficient environmental friendliness, easy product agglomeration, poor liquid-phase dispersibility, and lack of continuous production, making it difficult to meet the demands for high performance, greenness, and scalability.

Method used

A monodisperse nano-metal dispersion was prepared by using a supergravity reactor combined with plant extract as a reducing agent, and simultaneously introducing metal salt solution and plant extract through a peristaltic pump to carry out a reduction reaction. After centrifugation and washing, the mixture was ultrasonically dispersed.

Benefits of technology

It achieves monodisperse state of nano-metal particles in dispersion medium, with an average particle size of less than 10nm, regular morphology, no precipitation after 6 months of storage, applicable to various metal systems, suitable for large-scale production, and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120901279A_ABST
    Figure CN120901279A_ABST
Patent Text Reader

Abstract

The invention discloses a monodisperse nano-metal dispersion and a rapid continuous green synthesis method thereof. The rapid continuous green synthesis method of the monodisperse nano-metal dispersoid comprises the following steps that S1, plant materials are cleaned, dried, smashed and sieved, and plant powder is obtained; dissolving the obtained plant powder in a first solvent, placing in a water bath kettle, stirring and heating, then standing, cooling and filtering to obtain supernate marked as feed liquid A; s2, dissolving metal salt into a second solvent, and recording as feed liquid B; s3, starting the supergravity reactor; s4, the feed liquid A and the feed liquid B are simultaneously introduced into a supergravity reactor through a peristaltic pump for a reduction reaction, and a reaction liquid is obtained after the reaction; and S5, after the reaction liquid is centrifugally washed, solid particles are obtained, the solid particles are ultrasonically dispersed in a third solvent, and the monodisperse nano-metal dispersoid is obtained. The nano-metal is in a monodisperse state in the dispersion liquid, the average particle size is smaller than or equal to 10 nm, the morphology is regular, and no precipitate is generated after the nano-metal is stored for 6 months.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of nanomaterial preparation, and relates to the technical field of green synthesis of materials, in particular to a monodisperse nanometal dispersion and a rapid continuous green synthesis method thereof. BACKGROUND

[0002] Nanometal materials have a wide range of applications in the fields of environment, medicine and engineering due to their excellent physical and chemical properties. With the development of application requirements towards high efficiency, refinement and greenness, the synthesis process puts forward higher requirements on the particle size control, dispersion stability and environmental friendliness of nanometal materials.

[0003] At present, the preparation methods of metal nanoparticles mainly include physical methods (such as gas deposition, laser ablation, etc.) and chemical methods (such as liquid phase reduction, hydrothermal synthesis, etc.). Although the physical method can realize no chemical residues, it needs to be carried out under harsh conditions such as high temperature and high pressure, and the equipment is expensive, the energy consumption is huge, and it is difficult to scale up. The traditional chemical reduction method is simple in operation, high in reaction efficiency, and is widely used in laboratory preparation, but still has significant defects, such as the use of toxic and strong reducing agents such as sodium borohydride and hydrazine, which is easy to pollute the environment, and the product has limited stability and dispersion, and the agglomeration phenomenon is common, which is difficult to meet the green and industrialization needs.

[0004] In order to solve the above problems, researchers are actively exploring a more green, safe and controllable preparation path. Among them, the green synthesis method represented by plant extract gradually becomes an effective choice to replace the traditional route in recent years. Plant tissues and their extracts are rich in natural reducing components such as polyphenols, phenolic acids, aldehydes, proteins and terpenes, which can reduce metal ions to nanoparticles under mild conditions and have a stabilizing effect. Compared with microbial method, the plant extract synthesis system is easier to control, simple in process and free of pathogenic risk, and is suitable for large-scale production.

[0005] At present, a number of studies on the preparation of metal nanomaterials have made certain progress. For example, Chinese Patent Application CN110883339A discloses a metal powder preparation method based on a supergravity rotating packed bed, which can realize efficient preparation of various metals such as Cu, Fe, Ni or Co, and exhibits good particle size control ability and reaction efficiency. However, this method is mainly applied to the acquisition of powder precipitates, and cannot solve the key problem of forming stable dispersions of metal nanoparticles in liquid phase, and the reducing agent used still relies on traditional chemical systems, which is not green enough. For another example, Chinese Patent Application CN111320193A proposes a multi-step process for synthesizing metal nanoparticles by combining sol-gel transformation, high-temperature calcination and reduction treatment. Although this method can prepare metal oxide and metal nanoparticles with uniform particle size and good crystallinity, the overall process is complex and needs to go through multiple steps such as organic sol preparation, gel film formation, high-temperature calcination, water washing and calcination reduction, which not only has high energy consumption and complicated operation, but also the obtained product is mainly in the form of dry powder, which is difficult to meet the needs of liquid phase stable dispersion and continuous production.

[0006] In summary, the existing preparation methods generally have problems such as complex process flow, lack of greenness, easy agglomeration of products, poor liquid phase dispersibility, lack of continuity and multi-metal universality, which cannot meet the current comprehensive needs of high performance, greenness and scalable preparation of nanometal materials. Therefore, it is urgent to develop a new strategy for preparing nanometal materials with simple process, low toxicity, controllable particle size, good dispersibility and applicability to various metal systems. SUMMARY

[0007] The first technical problem to be solved by the present application is to provide a monodisperse nanometal dispersion. The nanometal is in a monodisperse state in the dispersion liquid, has an average particle size of ≦10 nm, uniform particle size, regular morphology, no precipitation after 6 months of storage, and good stability.

[0008] The second problem to be solved by the present application is to provide a rapid, continuous and green synthesis method of monodisperse nanometal dispersion. This method does not require high-temperature hydrothermal treatment, has a simple preparation process and short reaction time, and the obtained metal nanoparticles are in a monodisperse state in the dispersion medium, and are suitable for high-stability and large-scale synthesis of various metal particles, and have good particle size controllability, process universality and green environmental protection performance.

[0009] To solve the above-mentioned first technical problem, the technical solution adopted by the present application is as follows:

[0010] A monodisperse nanometal dispersion includes a nanometer zero-valent iron dispersion, a nanometer nickel dispersion, a nanometer copper dispersion, a nanometer palladium dispersion, a nanometer platinum dispersion or a nanometer gold dispersion;

[0011] wherein,

[0012] The solid content of the nano zero-valent iron is 0.1wt.%-40wt.% and the average particle size is 1-10nm.

[0013] The solid content of the nano nickel is 0.1wt.%-30wt.% and the average particle size is 5-10nm.

[0014] The solid content of the nano copper is 0.1wt.%-30wt.% and the average particle size is 2-10nm.

[0015] The solid content of the nano palladium is 0.1wt.%-10wt.% and the average particle size is 2-10nm.

[0016] The solid content of the nano platinum is 0.01wt.%-5wt.% and the average particle size is 2-10nm.

[0017] The solid content of the nano gold is 0.01wt.%-5wt.% and the average particle size is 1-5nm.

[0018] To solve the above-mentioned second technical problem, the technical scheme adopted by the present application is as follows:

[0019] A rapid and continuous green synthesis method of monodisperse nano metal dispersion includes the following steps:

[0020] S1, the plant material is washed, dried and crushed, and then sieved to obtain plant powder; the obtained plant powder is dissolved in a first solvent, stirred and heated in a water bath, then cooled and filtered to obtain a supernatant, which is denoted as solution A;

[0021] S2, the metal salt is dissolved in a second solvent, denoted as solution B;

[0022] S3, the supergravity reactor is started;

[0023] S4, solution A and solution B are simultaneously introduced into the supergravity reactor through a peristaltic pump for reduction reaction, and a reaction solution is obtained after reaction;

[0024] S5, the reaction solution is centrifuged and washed to obtain solid particles, which are dispersed in a third solvent by ultrasonic to obtain a monodisperse nano metal dispersion.

[0025] As a further improvement of the technical scheme, in step S1, the plant material is any one or more of citrus fruit peels; the citrus fruit is one of orange, grapefruit, ugly orange, gold orange, lemon and lime.

[0026] Preferably, in step S1, the first solvent is a mixed solution of water and an organic solvent; the organic solvent is selected from one or more of methanol, ethanol, acetone, ethyl acetate and ethylene glycol.

[0027] Preferably, in step S1, the volume ratio of water to organic solvent in the mixed solution of water and organic solvent is 1:10-10:1.

[0028] Preferably, in step S1, the solid-liquid ratio of the plant powder to the first solvent is 1:10-1:30 g / mL.

[0029] Preferably, in step S1, the temperature of the stirring and heating is 30-80°C, the stirring rate is 200-800 r / min, and the stirring and heating time is 0.5-12 h.

[0030] Preferably, in step S1, the mesh size of the pulverized and sieved plant powder is 100-120 mesh.

[0031] As a further improvement of the technical solution, in step S2, the metal salt is selected from one of the following: an iron source for preparing nano zero-valent iron, a nickel source for preparing nano nickel, a copper source for preparing nano copper, a palladium source for preparing nano palladium, a platinum source for preparing nano platinum, and a gold source for preparing nano gold; the iron source for preparing nano zero-valent iron is selected from one or more of the following: ferrous chloride tetrahydrate, ferric chloride hexahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and iron acetylacetone; the nickel source for preparing nano nickel is selected from one or more of the following: nickel sulfate hexahydrate, nickel nitrate hexahydrate, and nickel chloride tetrahydrate; the copper source for preparing nano copper is selected from one or more of the following: copper sulfate pentahydrate, copper nitrate trihydrate, copper acetate monohydrate, and copper chloride dihydrate; the palladium source for preparing nano palladium is selected from one or more of the following: palladium chloride, palladium nitrate, and palladium acetate; the platinum source for preparing nano platinum is selected from one or more of the following: chloroplatinic acid, potassium tetrachloroplatinate, potassium hexachloroplatinate, and platinum nitrate; and the gold source for preparing nano gold is selected from one or more of the following: chloroauric acid and gold chloride.

[0032] Preferably, in step S2, the concentration of the metal salt is 0.01-0.5 mol / L; more preferably, the concentration of the metal salt is 0.02-0.4 mol / L; and most preferably, the concentration of the metal salt is 0.02-0.3 mol / L.

[0033] Preferably, in step S2, the second solvent is water, an organic solvent, or a mixed solution of water and an organic solvent; and the organic solvent is selected from one or more of the following: methanol, ethanol, n-propanol, isopropanol, and ethylene glycol.

[0034] Preferably, in step S2, the volume ratio of water to organic solvent in the mixed solution of water and organic solvent is 1:0.5-1:5.

[0035] As a further improvement of the technical solution, in step S3, the high gravity reactor is selected from one of the following: high gravity rotating packed bed reactor, high gravity zigzag rotating bed reactor, fixed-rotor high gravity rotating bed reactor, spiral channel high gravity rotating reactor or rotating disc high gravity rotating bed reactor; the rotor speed of the high gravity reactor is 500-2500 rpm.

[0036] As a further improvement of the technical solution, in step S4, the feeding rate of the feed liquid A is 50-500 mL / min; the feeding rate of the feed liquid B is 50-500 mL / min; the ratio of the feeding rates of the feed liquid A and the feed liquid B is 1:0.5-1:2.

[0037] As a further improvement of the technical solution, in step S5, the centrifugal washing speed is 8000-12000 rpm, the centrifugal washing time is 5-30 min; the washing agent is one or more of water, methanol, ethanol or acetone; the washing times is 3-5 times; the ultrasonic dispersion time is 0.5-12 h.

[0038] Preferably, in step S5, the third solvent is one or more of the following: water, methanol, ethanol, ethylene glycol, n-propanol, isopropanol, acetonitrile.

[0039] Any range recited in the present application includes the end values and any intervening value and any sub-range comprised between the end values or intervening values.

[0040] Unless otherwise specified, each raw material in the present application can be obtained by commercial purchase, and the equipment used in the present application can adopt conventional equipment in the field or refer to the existing technology in the field.

[0041] Compared with the prior art, the present application has the following beneficial effects:

[0042] 1) The process of the present application is simple, uses natural plant resources to replace expensive and toxic reducing agents such as sodium borohydride, is green and environmentally friendly, significantly reduces environmental burden and operation risk, and produces green and efficient products.

[0043] 2) The method of the present application does not require any additional modifier, and the prepared nano metal particles have uniform particle size, good dispersibility, and no precipitation after storage for 6 months.

[0044] 3) The preparation method of monodisperse nano metal dispersion proposed in the present application can be used to prepare a variety of nano metal particles, including Fe, Ni, Cu, Pd, Pt or Au, and has strong process versatility.

[0045] 4) The present application can greatly strengthen the mass transfer and micro-mixing process of the reaction by using the super gravity technology, overcomes the problems of low mass transfer efficiency, uneven mixing, large local concentration gradient and uncontrollable nucleation process in the traditional stirred tank, and can prepare high-stability monodisperse nanometal dispersion, which is suitable for large-scale production. BRIEF DESCRIPTION OF DRAWINGS

[0046] The specific embodiments of the present application will be further described in detail below with reference to the accompanying drawings

[0047] Figure 1 A schematic diagram of a super gravity reactor used in the present application is shown;

[0048] Figure 2 The physical map and transmission electron microscope map of the product prepared in Example 1 are shown;

[0049] Figure 3 The UV-Vis spectrum of the product prepared in Example 2 is shown;

[0050] Figure 4 The physical map and transmission electron microscope map of the product prepared in Example 5 are shown;

[0051] Figure 5 The UV-Vis spectrum of the product prepared in Example 5 is shown;

[0052] Figure 6 The physical map and transmission electron microscope map of the product prepared in Example 7 are shown;

[0053] Figure 7 The UV-Vis spectrum of the product prepared in Example 7 is shown;

[0054] Figure 8 The transmission electron microscope map of the product prepared in Comparative Example 1 is shown;

[0055] Figure 9 The transmission electron microscope map of the product prepared in Comparative Example 2 using green tea as the reducing agent is shown;

[0056] Figure 10 The transmission electron microscope map of the product prepared in Comparative Example 2 using eucalyptus leaves as the reducing agent is shown;

[0057] Figure 11 The transmission electron microscope map of the product prepared in Comparative Example 2 using green coffee beans as the reducing agent is shown;

[0058] Figure 12 The transmission electron microscope map of the product prepared in Comparative Example 3 is shown;

[0059] Figure 13 The transmission electron microscope map of the product prepared in Comparative Example 4 is shown;

[0060] Figure 14Transmission electron micrograph of the product obtained in Comparative Example 5;

[0061] Figure 15 Transmission electron micrograph of the product obtained in Comparative Example 6;

[0062] Figure 16 Transmission electron micrograph of the product obtained in Comparative Example 7;

[0063] Figure 17 Transmission electron micrograph of the product obtained in Comparative Example 8. DETAILED DESCRIPTION

[0064] In order to more clearly illustrate the present application, the present application will be further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the specific descriptions below are illustrative rather than limiting, and should not limit the scope of protection of the present application.

[0065] As one aspect of the present application, the present application is a monodisperse nanometal dispersion, including a nanometer zero-valent iron dispersion, a nanometer nickel dispersion, a nanometer copper dispersion, a nanometer palladium dispersion, a nanometer platinum dispersion, or a nanometer gold dispersion;

[0066] wherein,

[0067] The nanometer zero-valent iron has a solid content of 0.1wt.%-40wt.% and an average particle size of 1-10nm;

[0068] The nanometer nickel has a solid content of 0.1wt.%-30wt.% and an average particle size of 5-10nm;

[0069] The nanometer copper has a solid content of 0.1wt.%-30wt.% and an average particle size of 2-10nm;

[0070] The nanometer palladium has a solid content of 0.1wt.%-10wt.% and an average particle size of 2-10nm;

[0071] The nanometer platinum has a solid content of 0.01wt.%-5wt.% and an average particle size of 2-10nm;

[0072] The nanometer gold has a solid content of 0.01wt.%-5wt.% and an average particle size of 1-5nm.

[0073] As another aspect of the present application, the present application is a rapid continuous green synthesis method of a monodisperse nanometal dispersion, including the following steps:

[0074] S1, washing and drying the plant material, crushing and sieving to obtain plant powder; dissolving the obtained plant powder in a first solvent, placing in a water bath for stirring and heating, then standing and cooling, filtering to obtain supernatant, denoted as feed liquid A;

[0075] S2, dissolving the metal salt in a second solvent, denoted as feed liquid B;

[0076] S3, starting the high gravity reactor;

[0077] S4, feeding the feed liquid A and the feed liquid B into the high gravity reactor through the peristaltic pump for reduction reaction, and obtaining a reaction solution after the reaction;

[0078] S5, obtaining solid particles after centrifugal washing of the reaction solution, and ultrasonic dispersion in a third solvent to obtain a monodisperse nanometal dispersion.

[0079] The high gravity reactor used in the present application is available, for example, the published patent (publication number: CN2221437A, invention name "rotary bed high gravity field device for strengthening transfer reaction"); Figure 1 A high gravity reactor used in the present application is shown in the schematic diagram. The specific embodiments are described as follows: starting the high gravity reactor device, adjusting the rotation speed to make the rotation speed of the rotor in the high gravity reactor device reach the preset value; feeding the feed liquid A into the feed inlet 1 of the high gravity reactor through the peristaltic pump; feeding the feed liquid B into the feed inlet 2 of the high gravity reactor through the peristaltic pump; the rotor packing 3 in the high gravity reactor is driven by the motor 4 and rotates at high speed, thereby obtaining a high gravity environment; the feed liquid A and the feed liquid B are sprayed into the inner edge of the rotor packing of the high gravity reactor through the liquid distributor on the feed pipe, and then collide with the packing and enter the inside of the packing; the feed liquid A and the feed liquid B entering the inside of the packing are divided, broken and torn by the wire mesh packing, and then a large number of rapidly updated liquid surfaces are generated, which greatly strengthens the mass transfer process between molecules, shortens the crystal nucleus growth time after the reaction of the reactants, and thereby effectively controls the particle size and morphology of the nucleated particles; the solution after the reaction flows out from the liquid phase discharge port 5 at the lower part of the high gravity reactor, and a series of monodisperse nanometal dispersions are prepared after centrifugal washing and ultrasonic treatment.

[0080] According to some embodiments of the present application, in step S1, the plant material is any one or more of citrus fruit peels; and the citrus fruit is one of orange, grapefruit, ugly orange, gold orange, lemon, lime.

[0081] According to some embodiments of the present application, in step S1, the first solvent is a mixed solution of water and an organic solvent; and the organic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, acetone, ethyl acetate, ethylene glycol.

[0082] According to some embodiments of the present application, in step S1, the ratio of water to organic solvent in the mixed solution of water and organic solvent is 1:10-10:1.

[0083] According to some embodiments of the present application, in step S1, the solid-liquid ratio of the plant powder to the first solvent is 1:10-1:30 g / mL.

[0084] According to some embodiments of the present application, in step S1, the temperature of the stirring and heating is 30-80℃, the stirring rate is 200-800 r / min, and the stirring and heating time is 0.5-12 h.

[0085] According to some embodiments of the present application, in step S1, the mesh size of the pulverization and sieving is 100-120 mesh.

[0086] According to some embodiments of the present application, in step S2, the metal salt is selected from one of the following: an iron source for preparing nano zero-valent iron, a nickel source for preparing nano nickel, a copper source for preparing nano copper, a palladium source for preparing nano palladium, a platinum source for preparing nano platinum, and a gold source for preparing nano gold; the iron source for preparing nano zero-valent iron is selected from one or more of the following: ferrous chloride tetrahydrate, ferric chloride hexahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and iron acetylacetonate; the nickel source for preparing nano nickel is selected from one or more of the following: nickel sulfate hexahydrate, nickel nitrate hexahydrate, and nickel chloride tetrahydrate; the copper source for preparing nano copper is selected from one or more of the following: copper sulfate pentahydrate, copper nitrate trihydrate, copper acetate monohydrate, and copper chloride dihydrate; the palladium source for preparing nano palladium is selected from one or more of the following: palladium chloride, palladium nitrate, and palladium acetate; the platinum source for preparing nano platinum is selected from one or more of the following: chloroplatinic acid, potassium tetrachloroplatinate, potassium hexachloroplatinate, and platinum nitrate; and the gold source for preparing nano gold is selected from one or more of the following: chloroauric acid and gold chloride.

[0087] According to some embodiments of the present application, in step S2, the concentration of the metal salt is 0.01-0.5 mol / L; more preferably, the concentration of the metal salt is 0.02-0.4 mol / L; and most preferably, the concentration of the metal salt is 0.02-0.3 mol / L.

[0088] According to some embodiments of the present application, in step S2, the second solvent is water, an organic solvent, or a mixed solution of water and an organic solvent; and the organic solvent is selected from one or more of the following: methanol, ethanol, n-propanol, isopropanol, and ethylene glycol.

[0089] According to some embodiments of the present application, in step S2, the volume ratio of water to the organic solvent in the mixed solution of water and the organic solvent is 1:0.5-1:5.

[0090] According to some embodiments of the present application, in step S3, the high gravity reactor is selected from one of the following: a high gravity rotating packed bed reactor, a high gravity rotating bed reactor with baffles, a high gravity rotating bed reactor with fixed-rotor, a high gravity rotating reactor with spiral channel, or a high gravity rotating bed reactor with rotating disc; the rotation speed of the rotor of the high gravity reactor is 500-2500 rpm.

[0091] According to some embodiments of the present application, in step S4, the feeding rate of the feed liquid A is 50-500 mL / min; the feeding rate of the feed liquid B is 50-500 mL / min; the ratio of the feeding rates of the feed liquid A and the feed liquid B is 1:0.5-1:2.

[0092] According to some embodiments of the present application, in step S5, the rotation speed of the centrifugal washing is 8000-12000 rpm, the centrifugal washing time is 5-30 min; the washing agent is one or more of water, methanol, ethanol or acetone; the washing times is 3-5 times; the ultrasonic dispersion time is 0.5-12 h.

[0093] According to some embodiments of the present application, in step S5, the third solvent is one or more of the following: water, methanol, ethanol, ethylene glycol, n-propanol, isopropanol, acetonitrile.

[0094] Example 1

[0095] A method for preparing a monodisperse nano zero-valent iron dispersion, comprising the following steps:

[0096] 1) preparing a plant extract: orange peels are washed with water and ethanol, dried in an 80℃ oven, crushed, and sieved through a 100 mesh sieve; 5g of the obtained plant powder is added to 20mL of water and 30mL of ethanol, placed in a 60℃ water bath, and magnetically stirred for 1h; after the stirring is completed, the mixture is allowed to cool and stand, and the supernatant is obtained by suction filtration, and is recorded as feed liquid A;

[0097] 2) preparing a metal salt solution: 6.95g of ferrous sulfate heptahydrate is dissolved in 50mL of water, and is recorded as feed liquid B;

[0098] 3) setting the rotation speed of the rotor to 500 rpm, and starting the high gravity reactor;

[0099] 4) feeding the feed liquid A and the feed liquid B into the high gravity reactor through a peristaltic pump at the same time, wherein the feeding rate of the feed liquid A is 100mL / min, and the feeding rate of the feed liquid B is 100mL / min, to perform a reduction reaction, and obtain a reaction liquid;

[0100] 5) The obtained reaction solution was centrifuged at 12000 r / min for 10 min, washed with water and ethanol alternately for 3 times, and the solid particles were dispersed in ethanol by ultrasonic to obtain a nano zero-valent iron / ethanol phase dispersion.

[0101] Figure 2 The transmission electron microscope image and the actual image of the nano zero-valent iron dispersion prepared in this embodiment show that the average particle size of the obtained nano zero-valent iron / ethanol phase dispersion particles is 5 nm, the morphology is spherical, and it has monodispersity; the upper right is the dispersion actual photo, the solid content is 10 wt.%, no precipitation is generated after standing for 6 months, and the dispersion remains stable.

[0102] Example 2

[0103] A preparation method of a monodisperse nano zero-valent iron dispersion, comprising the following steps:

[0104] 1) Preparation of plant extract solution: the Shanyan orange peel was washed with water and ethanol, dried in an 80°C oven, crushed, and sieved through a 100 mesh sieve. 5 g of the obtained plant powder was added to 50 mL of water and 50 mL of ethanol, and placed in a 80°C water bath for magnetic stirring for 2 h. After the end of the stirring, the supernatant was obtained by filtration, and was recorded as solution A;

[0105] 2) Preparation of metal salt solution: 1.35 g of iron chloride hexahydrate was dissolved in 50 mL of water, and was recorded as solution B;

[0106] 3) The rotation speed of the rotor was set to 500 rpm, and the supergravity reactor was started;

[0107] 4) The solutions A and B were simultaneously fed into the supergravity reactor through a peristaltic pump, wherein the feeding rate of solution A was 200 mL / min, and the feeding rate of solution B was 200 mL / min, to carry out a reduction reaction, and a reaction solution was obtained;

[0108] 5) The obtained reaction solution was centrifuged at 10000 r / min for 15 min, washed with water and ethanol alternately for 3 times, and the solid particles were dispersed in water by ultrasonic to obtain a nano zero-valent iron / water phase dispersion.

[0109] Figure 3 The UV-Vis absorption spectrum of the nano zero-valent iron dispersion prepared in this embodiment is shown in the figure. As can be seen from the figure, the absorption peak is mainly concentrated in the 200-300 nm waveband, and a wide absorption peak appears at a higher wavelength, indicating that highly dispersed nano zero-valent iron is formed, which is consistent with the characteristics of the target product.

[0110] Example 3

[0111] A preparation method of a monodisperse nano nickel dispersion, comprising the following steps:

[0112] 1) Preparation of plant extract: Wash lemon peel with water and ethanol, dry it in an 80℃ oven and then crush it. Pass it through a 100-mesh sieve. Take 5g of the obtained plant powder and add it to 100mL of water and 50mL of ethanol. Place it in a 70℃ water bath and stir magnetically for 5h. After the end, let it stand and cool, filter it to obtain the supernatant, and record it as liquid A.

[0113] 2) Preparation of metal salt solution: Dissolve 0.59g of nickel chloride hexahydrate in 50mL of water, and denote this as solution B;

[0114] 3) Set the rotor speed to 2500 rpm and start the hypergravity reactor;

[0115] 4) Feed solution A and feed solution B are simultaneously fed into the centrifugal reactor using a peristaltic pump. The feed rate of feed solution A is 100 mL / min and the feed rate of feed solution B is 100 mL / min. The reduction reaction is carried out to obtain the reaction solution.

[0116] 5) Centrifuge the obtained reaction solution at 12000 r / min for 10 min, wash it three times alternately with water and ethanol, and obtain solid particles ultrasonically dispersed in ethanol to obtain nano-nickel / ethanol phase dispersion.

[0117] Example 4

[0118] A method for preparing a monodisperse copper nanoparticle dispersion includes the following steps:

[0119] 1) Preparation of plant extract: Wash grapefruit peel with water and ethanol, dry it in an 80℃ oven and then crush it. Pass it through a 100-mesh sieve. Take 5g of the obtained plant powder and add it to 100mL of water and 50mL of methanol. Place it in a 60℃ water bath and stir magnetically for 6h. After the end, let it stand and cool, filter it to obtain the supernatant, and record it as liquid A.

[0120] 2) Preparation of metal salt solution: Dissolve 1.25g of copper sulfate pentahydrate in 50mL of water, and label it solution B;

[0121] 3) Set the rotor speed to 2500 rpm and start the hypergravity reactor;

[0122] 4) Feed solution A and feed solution B are simultaneously fed into the centrifugal reactor using a peristaltic pump. The feed rate of feed solution A is 200 mL / min and the feed rate of feed solution B is 200 mL / min. The reduction reaction is carried out to obtain the reaction solution.

[0123] 5) Centrifuge the obtained reaction solution at 10000 r / min for 8 min, and wash it three times alternately with water and methanol to obtain solid particles ultrasonically dispersed in methanol, thus obtaining a nano-copper / methanol phase dispersion.

[0124] Example 5

[0125] A method for preparing monodisperse nanometer palladium dispersion, comprising the following steps:

[0126] 1) preparing plant extract solution A: orange peel is washed with water and ethanol, dried in an 80℃ oven, crushed, and passed through a 100 mesh sieve. 5g of the obtained plant powder is added to 25mL of water and 25mL of ethanol, placed in a 60℃ water bath, and magnetically stirred for 1h. After the end of the stirring, the solution is allowed to cool and stand, and the supernatant is obtained by suction filtration, and is recorded as solution A;

[0127] 2) preparing metal salt solution B: 0.71g of palladium chloride is dissolved in 50mL of water, and is recorded as solution B;

[0128] 3) setting the rotation speed of the rotor to 500rpm, and starting the high gravity reactor;

[0129] 4) feeding solution A and solution B into the high gravity reactor through a peristaltic pump, wherein the feeding rate of solution A is 100mL / min, and the feeding rate of solution B is 100mL / min, to carry out a reduction reaction, and obtain a reaction solution;

[0130] 5) centrifuging the obtained reaction solution at 12000r / min for 10min, and washing with water and ethanol alternately for 3 times, to obtain solid particles which are dispersed in water, and obtain nanometer palladium / water phase dispersion.

[0131] Figure 4 The transmission electron microscope image and the actual image of the nanometer palladium dispersion prepared in this example show that the average particle size of the obtained nanometer palladium / water phase dispersion is 6nm, and the dispersion is good; the upper right is the dispersion actual photo, and the solid content is 1wt.%.

[0132] Figure 5 The UV-Vis absorption spectrum of the nanometer palladium dispersion prepared in this example is shown in the figure. As can be seen from the figure, there is no obvious sharp absorption peak in the wavelength range, but a gently declining wideband absorption curve, which is consistent with the typical spectral response of nanometer palladium particles in the ultraviolet-visible region.

[0133] Example 6

[0134] A method for preparing monodisperse nanometer platinum dispersion, comprising the following steps:

[0135] 1) preparing plant extract solution A: orange peel is washed with water and ethanol, dried in an 80℃ oven, crushed, and passed through a 100 mesh sieve. 5g of the obtained plant powder is added to 25mL of water and 25mL of ethanol, placed in a 60℃ water bath, and magnetically stirred for 1h. After the end of the stirring, the solution is allowed to cool and stand, and the supernatant is obtained by suction filtration, and is recorded as solution A;

[0136] 2) Preparation of metal salt solution: 3.38 g of potassium tetrachloroplatinate was dissolved in 50 mL of water, denoted as solution B;

[0137] 3) The rotation speed of the rotor was set to 500 rpm, and the high gravity reactor was started;

[0138] 4) Solution A and solution B were simultaneously fed into the high gravity reactor through a peristaltic pump, wherein the feeding rate of solution A was 200 mL / min, and the feeding rate of solution B was 200 mL / min, and a reduction reaction was carried out to obtain a reaction liquid;

[0139] 5) The obtained reaction liquid was centrifuged at 10,000 r / min for 15 min by using a centrifuge, and was washed with water and ethanol alternately for 3 times to obtain solid particles, which were ultrasonically dispersed in water to obtain a nano platinum / water phase dispersion.

[0140] Example 7

[0141] A preparation method of a monodisperse nano gold dispersion, comprising the following steps:

[0142] 1) Preparation of plant extract solution: The gold orange peel was washed with water and ethanol, dried in an 80°C oven, and then crushed and sieved through a 100 mesh sieve. 5 g of the obtained plant powder was added to 90 mL of water and 10 mL of ethanol, and placed in a 80°C water bath for magnetic stirring for 2 h. After the end of the stirring, the solution was allowed to cool and stand, and then filtered to obtain a supernatant, denoted as solution A;

[0143] 2) Preparation of metal salt solution: 0.25 g of chloroauric acid was dissolved in 50 mL of water, denoted as solution B;

[0144] 3) The rotation speed of the rotor was set to 2000 rpm, and the high gravity reactor was started;

[0145] 4) Solution A and solution B were simultaneously fed into the high gravity reactor through a peristaltic pump, wherein the feeding rate of solution A was 200 mL / min, and the feeding rate of solution B was 200 mL / min, and a reduction reaction was carried out to obtain a reaction liquid;

[0146] 5) The obtained reaction liquid was centrifuged at 12,000 r / min for 10 min by using a centrifuge, and was washed with water and methanol alternately for 3 times to obtain solid particles, which were ultrasonically dispersed in ethanol to obtain a nano gold / ethanol phase dispersion.

[0147] Figure 6 The transmission electron microscope image and the actual image of the nano gold dispersion prepared in this embodiment can be seen that the average particle size of the obtained nano gold / ethanol phase dispersion particles is 2 nm, and the dispersibility is good; the upper right is the dispersion actual photograph thereof, and the solid content is 0.5 wt.%.

[0148] Figure 7 The UV-Vis absorption spectrum of the prepared nanogold dispersion in this example is shown in the figure. It can be seen from the figure that the prepared nanogold particles have an obvious absorption peak at a wavelength of about 550 nm, which is the surface plasmon resonance absorption peak of the nanogold particles, indicating that the nanogold particles are successfully generated.

[0149] Comparative Example 1

[0150] The nanoscale zero-valent iron dispersion is prepared by using the steps as described in Example 1, except that in step 1), the green plant extract is replaced by one or more of sodium borohydride and hydrazine hydrate.

[0151] Figure 8 The transmission electron micrograph and the actual product of the obtained product are shown in the figure.

[0152] As a result, when the common reducing agent sodium borohydride or hydrazine hydrate is selected as the reducing agent in step 1), the obtained nanoscale zero-valent iron particles have obvious chain-like agglomerated structure, large particle size, and poor system stability.

[0153] Comparative Example 2

[0154] The nanoscale zero-valent iron dispersion is prepared by using the steps as described in Example 1, except that in step 1), the orange peel is replaced by green tea, eucalyptus leaves or green coffee beans, respectively.

[0155] Figures 9-11 The transmission electron micrographs of the obtained products of the above three plant extracts are shown in the figure.

[0156] As a result, when the green tea, eucalyptus leaves or green coffee beans are used as the reducing agent in step 1), the obtained nanoscale zero-valent iron particles have wide particle size distribution, large particles, and obvious agglomeration phenomenon, and it is difficult to achieve good monodispersity, indicating that such reducing agents are not conducive to forming a highly dispersed and stable nanoparticle system.

[0157] Comparative Example 3

[0158] The nanoscale zero-valent iron dispersion is prepared by using the steps as described in Example 2, except that in step 1), 5 g of the obtained plant powder is added to 100 mL of water and 100 mL of ethanol.

[0159] Figure 12 The transmission electron micrograph of the obtained product is shown in the figure.

[0160] The result is that the reducing property of the prepared plant extract solution is too weak to completely reduce the nano zero-valent iron particles due to the too large solid-liquid ratio of the plant powder and the first solvent, i.e. 1:40 g / mL. It can be seen that the solid-liquid ratio in the preparation of the plant extract solution in the present application needs to be controlled within the preferred range, and the reducing property is too weak to successfully prepare the nano zero-valent iron particles when the solid-liquid ratio exceeds the range.

[0161] Comparative Example 4

[0162] The nano zero-valent iron dispersion was prepared by using the steps as described in Example 2, except that in step 1), 5 g of the obtained plant powder was added into 100 mL of water.

[0163] Figure 13 The transmission electron microscope image of the obtained product is shown in Figure 4.

[0164] The result is that no obvious nano particles are observed in the obtained product under the condition that the extraction solvent in step 1) is water, and the nano zero-valent iron particles with clear particle size and structural characteristics are not formed in the system.

[0165] Comparative Example 5

[0166] The nano zero-valent iron dispersion was prepared by using the steps as described in Example 2, except that in step 1), 5 g of the obtained plant powder was added into 100 mL of ethanol.

[0167] Figure 14 The transmission electron microscope image of the obtained product is shown in Figure 4.

[0168] The result is that the nano particle morphology is irregular, the particle size distribution is wide, and some particles have obvious agglomeration phenomenon when the extraction solvent in step 1) is ethanol. It can be seen that the extraction solvent needs to be controlled within the preferred range in the preparation of the plant extract solution in the present application, and it is difficult to extract sufficient active components when the extraction solvent exceeds the range, which leads to the failure to successfully prepare the nano zero-valent iron particles.

[0169] Comparative Example 6

[0170] The nano zero-valent iron dispersion was prepared by using the steps as described in Example 2, except that in step 2), 0.14 g of iron chloride hexahydrate was dissolved in 50 mL of water.

[0171] Figure 15 The transmission electron microscope image of the obtained product is shown in Figure 4.

[0172] As a result, no uniform nanoparticle structure is formed in the product due to the too low concentration of the metal salt solution, 0.01 mol / L, and the number of particles generated in the reaction system is small, and no obvious particle generation is observed in some areas. Therefore, the initial concentration of the metal salt in the present application needs to be controlled within the preferred range, and when the concentration is lower than the range, it will be not conducive to the stable generation of the nano zero-valent iron particles.

[0173] Comparative Example 7

[0174] The nano zero-valent iron dispersion was prepared by the steps as described in Example 2, except that in step 2), 5.14 g of iron chloride hexahydrate was dissolved in 50 mL of water.

[0175] Figure 16 The transmission electron microscope image of the obtained product is shown in Figure 2.

[0176] As a result, the nanoparticle agglomeration phenomenon is serious and the particle size distribution is wide due to the too high concentration of the metal salt solution, 0.38 mol / L. Therefore, the concentration of the metal salt solution in the present application needs to be controlled within the most preferred range; when the concentration exceeds the range, the dispersion stability and structure controllability of the product will be reduced.

[0177] Comparative Example 8

[0178] The nano zero-valent iron dispersion was prepared by the steps as described in Example 2, except that the reaction device was a traditional stirred tank and the reaction time was 30 minutes.

[0179] Figure 17 The transmission electron microscope image of the obtained product is shown in Figure 2.

[0180] As a result, the nano zero-valent iron particles prepared by the traditional stirred tank have irregular morphology, large particle size and uneven distribution, and there is a certain degree of agglomeration between the particles.

[0181] In the preparation method of the present application, the selection and treatment of the plant material and the selection of the high gravity equipment constitute a whole technical solution of each parameter, and mutual cooperation can obtain the monodisperse nano metal dispersion of the present application. Any condition exceeding will result in the failure to achieve the purpose of the present application.

[0182] Obviously, the above examples of the present application are only examples for clearly illustrating the present application, and are not a limitation on the embodiments of the present application. Based on the above description, other different forms of changes or variations can be made by those skilled in the art. Here, all the embodiments cannot be exhausted. Any obvious changes or variations derived from the technical solutions of the present application still fall within the protection scope of the present application.

Claims

1. A monodisperse nanometal dispersion comprising a nanometer zero-valent iron dispersion, a nanometer nickel dispersion, a nanometer copper dispersion, a nanometer palladium dispersion, a nanometer platinum dispersion, or a nanometer gold dispersion; characterized by: wherein, the solid content of the nano zero-valent iron is 0.1wt.%-40wt.% and the average particle size is 1-10nm; the solid content of the nano nickel is 0.1wt.%-30wt.% and the average particle size is 5-10nm; the solid content of the nano copper is 0.1wt.%-30wt.% and the average particle size is 2-10nm; the solid content of the nano palladium is 0.1wt.%-10wt.% and the average particle size is 2-10nm; the solid content of the nano platinum is 0.01wt.%-5wt.% and the average particle size is 2-10nm; the solid content of the nano gold is 0.01wt.%-5wt.% and the average particle size is 1-5nm.

2. The process for rapid continuous green synthesis of monodispersed nanometal dispersions as claimed in claim 1 wherein, comprising the following steps: S1, washing and drying the plant material, crushing and sieving to obtain plant powder; dissolving the obtained plant powder in a first solvent, placing in a water bath for stirring and heating, then standing and cooling, filtering to obtain supernatant, denoted as feed liquid A; S2, dissolving metal salt in a second solvent, denoted as feed liquid B; S3, starting the supergravity reactor; S4, feeding feed liquid A and feed liquid B into the supergravity reactor through a peristaltic pump for reduction reaction, obtaining reaction liquid after reaction; S5, centrifugal washing the reaction liquid to obtain solid particles, ultrasonic dispersion in a third solvent to obtain monodisperse nano metal dispersion.

3. The process for rapid continuous green synthesis of monodispersed nanometallic dispersion as claimed in claim 2 wherein: In step S1, the plant material is any one or more of citrus fruit peels; the citrus fruit is one of orange, grapefruit, ugly orange, gold orange, lemon, lime.

4. The process for rapid continuous green synthesis of monodispersed nanometallic dispersion as claimed in claim 2 wherein: In step S1, the first solvent is a mixed solution of water and organic solvent; the organic solvent is selected from one or more of methanol, ethanol, acetone, ethyl acetate, ethylene glycol.

5. The process for rapid continuous green synthesis of monodispersed nanometallic dispersion as claimed in claim 4 wherein: In step S1, the volume ratio of water to organic solvent in the mixed solution of water and organic solvent is 1:10-10:

1.

6. The process for rapid continuous green synthesis of monodispersed nanometal dispersions as claimed in claim 2 wherein: In step S1, the solid-liquid ratio of plant powder to first solvent is 1:10-1:30g / mL; Preferably, in step S1, the stirring and heating temperature is 30-80℃, the stirring rate is 200-800r / min, and the stirring and heating time is 0.5-12h; Preferably, in step S1, the mesh size of the crushing and sieving is 100-120 mesh.

7. The process as claimed in claim 2, wherein the process is characterized by: The metal salt in step S2 is selected from one of the following: an iron source for preparing nano zero-valent iron, a nickel source for preparing nano nickel, a copper source for preparing nano copper, a palladium source for preparing nano palladium, a platinum source for preparing nano platinum, and a gold source for preparing nano gold; the iron source for preparing nano zero-valent iron is selected from one or more of the following: ferrous chloride tetrahydrate, ferric chloride hexahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and iron acetylacetonate; the nickel source for preparing nano nickel is selected from one or more of the following: nickel sulfate hexahydrate, nickel nitrate hexahydrate, and nickel chloride tetrahydrate; the copper source for preparing nano copper is selected from one or more of the following: copper sulfate pentahydrate, copper nitrate trihydrate, and copper acetate monohydrate; the palladium source for preparing nano palladium is selected from one or more of the following: palladium chloride, palladium nitrate, and palladium acetate; the platinum source for preparing nano platinum is selected from one or more of the following: chloroplatinic acid, potassium tetrachloroplatinate, and platinum nitrate; and the gold source for preparing nano gold is selected from one or more of the following: chloroauric acid and gold chloride. Preferably, in step S2, the concentration of the metal salt is 0.01-0.5 mol / L; more preferably, the concentration of the metal salt is 0.02-0.4 mol / L; and most preferably, the concentration of the metal salt is 0.02-0.3 mol / L. Preferably, in step S2, the second solvent is water, an organic solvent, or a mixed solution of water and an organic solvent; and the organic solvent is selected from one or more of the following: methanol, ethanol, n-propanol, and isopropanol. Preferably, in step S2, the volume ratio of water to the organic solvent in the mixed solution of water and the organic solvent is 1:0.5-1:

5.

8. The process for rapid continuous green synthesis of monodispersed nanometallic dispersion as claimed in claim 2 wherein: In step S3, the high-gravity reactor is selected from one of the following: a high-gravity rotating packed bed reactor, a high-gravity rotating bed reactor with a baffle, a high-gravity rotating bed reactor with a stator-rotor, a high-gravity rotating reactor with a spiral channel, or a high-gravity rotating bed reactor with rotating discs; and the rotation speed of the rotor of the high-gravity reactor is 500-2500 rpm.

9. The process for rapid continuous green synthesis of monodispersed nanometallic dispersion as claimed in claim 2 wherein: In step S4, the feeding rate of the feed liquid A is 50-500 mL / min; the feeding rate of the feed liquid B is 50-500 mL / min; and the ratio of the feeding rates of the feed liquid A and the feed liquid B is 1:0.5-1:

2.

10. The process for rapid continuous green synthesis of monodispersed nanometal dispersions as claimed in claim 2 wherein: In step S5, the rotation speed for centrifugal washing is 8000-12000 rpm, the centrifugal washing time is 5-30 min, the washing agent is one or more of the following: water, methanol, ethanol, and acetone, the washing times is 3-5 times, and the ultrasonic dispersion time is 0.5-12 h. Preferably, in step S5, the third solvent is one or more of the following: water, methanol, ethanol, ethylene glycol, n-propanol, isopropanol, and acetonitrile.

Citation Information

Patent Citations

  • Method for preparing ultrafine metal powder

    CN110883339A

  • Metal oxide nanoparticles and preparation method of metal oxide nanoparticles

    CN111320193A